Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Comprehensive site screening and selection for offshore CO2 storage in the Early Miocene formations of the eastern Gunsan Basin, Yellow Sea - Kyoung-Jin Kim; Moohee Kang; Snons Cheong; Kue-Young Kim; In-Sun Song; Kwanghyun Kim (Marine and Petroleum Geology, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In-situ Hf/Zr co-doped Fe2O3 nanorod decorated with CuOx/CoOx: Enhanced photocatalytic performance for antibacterial and organic pollutants - In-Seon Hwang; Mahadeo A. Mahadik; Periyasamy Anushkkaran; Min Seok Song; You Jin Jo; Weon-Sik Chae; Jung-Hee Park; Sun Hee Choi; Jum Suk Jang (Chemosphere, 2024)

In situ fabrication of Ag decorated porous ZnO photocatalyst via inorganic–organic hybrid transformation for degradation of organic pollutant and bacterial inactivation - Min Seok Song; Ruturaj P. Patil; In Seon Hwang; Mahadeo A. Mahadik; Tae-Hu Jang; Byung Taek Oh; Weon-Sik Chae; Sun Hee Choi; Hyun Hwi Lee; Jum Suk Jang (Chemosphere, 2023)

Microbial succession during button mushroom (Agaricus bisporus) production evaluated via high-throughput sequencing - Ga-Hee Ban; Jin-Hee Kim; Sun Ae Kim; Min Suk Rhee; Song Yi Choi; In Jun Hwang; Se-Ri Kim (Food Microbiology, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Influence of ultrafast microwave deposition on morphology and growth mechanism of WO3 nanosheet photoanode for efficient bacterial inactivation and decomposition of organic pollutants - In-Seon Hwang; Mahadeo A. Mahadik; Min Seok Song; Se-Won Lee; Byung-Taek Oh; Hyun Hwi Lee; Weon-Sik Chae; Sun Hee Choi; Jum Suk Jang (Journal of Environmental Chemical Engineering, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

Pollen-mediated flow of bar gene in transgenic herbicide-resistant turf grass Zoysia japonica - Hong-Gyu Kang; Ok-Chul Chung; Tae-Woong Bae; Hyeon-Jin Sun; In-Ja Song; Kee Woong Park; Pyung-Ok Lim; Jaechun Lee; Yong-Eok Lee; Pill-Soon Song; Hyo-Yeon Lee (Plant Biotechnology Reports, 2021)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

High-throughput phenotyping platform for analyzing drought tolerance in rice - Song Lim Kim; Nyunhee Kim; Hongseok Lee; Eungyeong Lee; Kyeong-Seong Cheon; Minsu Kim; JeongHo Baek; Inchan Choi; Hyeonso Ji; In Sun Yoon; Ki-Hong Jung; Taek-Ryoun Kwon; et al. (Planta, 2020)
Main conclusion A new imaging platform was constructed to analyze drought-tolerant traits of rice. Rice was used to quantify drought phenotypes through image-based parameters and analyzing tools. Abstract Climate change has increased the frequency and severity of drought, which limits crop production worldwide. Developing new cultivars with increased drought tolerance and short breeding cycles is critical. However, achieving this goal requires phenotyping a large number of breeding populations in a short time and in an accurate manner. Novel cutting-edge technologies such as those based on remote sensors are being applied to solve this problem. In this study, new technologies were applied to obtain and analyze imaging data and establish efficient screening platforms for drought tolerance in rice using the drought-tolerant mutant osphyb . Red–Green–Blue images were used to predict plant area, color, and compactness. Near-infrared imaging was used to determine the water content of rice, infrared was used to assess plant temperature, and fluorescence was used to examine photosynthesis efficiency. DroughtSpotter technology was used to determine water use efficiency, plant water loss rate, and transpiration rate. The results indicate that these methods can detect the difference between tolerant and susceptible plants, suggesting their value as high-throughput phenotyping methods for short breeding cycles as well as for functional genetic studies of tolerance to drought stress.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Twelve-year trend in the use of zolpidem and physicians’ non-compliance with recommended duration: a Korean national health insurance database study - Yunjeung Jang; Inmyung Song; In-Sun Oh; Ju-Young Shin (European Journal of Clinical Pharmacology, 2019)

Factors affecting the public awareness and behavior on antibiotic use - Kyungmin Huh; Doo Ryeon Chung; So Hyun Kim; Sun Young Cho; Young Eun Ha; Cheol-In Kang; Kyong Ran Peck; Jae-Hoon Song (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Endogenous TRPV4 Expression of a Hybrid Neuronal Cell Line N18D3 and Its Utilization to Find a Novel Synthetic Ligand - Sungjae Yoo; Seung-In Choi; Seul Lee; Jiho Song; Chungmi Yang; Sangsu Bang; Seung Up Kim; Kyung Hoon Min; Sun Wook Hwang (Journal of Molecular Neuroscience, 2017)

Local injection of granulocyte-colony stimulating factor accelerates wound healing in a rat excisional wound model - Guang-Yin Shen; In-Hwa Park; Yi-Sun Song; Hyun-Woo Joo; Yonggu Lee; Jeong-Hun Shin; Kyung-Soo Kim; Hyuck Kim (Tissue Engineering and Regenerative Medicine, 2016)

Investigation into effects of transgenic glufosinate-resistant Zoysia grasses with herbicide application on bacterial communities under field conditions - Yong-Eok Lee; Sun Hwa Lee; Gil-Do Ryu; Hong-Gyu Kang; Yong-Ik Kwon; Hyeon-Jin Sun; Kee Woong Park; Bumkyu Lee; In-Ja Song; Pyung-Ok Lim; Hyo-Yeon Lee (Journal of Plant Biology, 2015)

Monthly metabolic changes and PLS prediction of carotenoid content of citrus fruit by combined Fourier transform infrared spectroscopy and quantitative HPLC analysis - Suk Weon Kim; Myung Suk Ahn; Yong Kook Kwon; Seung Yeob Song; Jae Kwang Kim; Sun-Hwa Ha; In-Jung Kim; Jang R. Liu (Plant Biotechnology Reports, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Dietary aflatoxin B1 intake, genetic polymorphisms of CYP1A2, CYP2E1, EPHX1, GSTM1, and GSTT1, and gastric cancer risk in Korean - Sang-Yong Eom; Dong-Hyuk Yim; Yanwei Zhang; Jung-Kuk Yun; Sun In Moon; Hyo-Yung Yun; Young-Jin Song; Sei-Jin Youn; Taisun Hyun; Joo-Seung Park; Byung Sik Kim; Jong-Young Lee; et al. (Cancer Causes & Control, 2013)

Normative data for neuromuscular assessment of the hand–arm vibration syndrome and its retrospective applications in Korean male workers - Ryeok Ahn; Cheol-In Yoo; Hun Lee; Chang-Sun Sim; Joo Hyun Sung; Jae-Kook Yoon; Song-Woo Shin (International Archives of Occupational and Environmental Health, 2013)

Deduced sequences of the membrane fusion and attachment proteins of canine distemper viruses isolated from dogs and wild animals in Korea - Chae-Wun Bae; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Nak-Hyung Lee; Kun-Ho Seo; Young-Sun Kang; Choi-Kyu Park; In-Soo Choi (Virus Genes, 2013)

Neural substrates of acupuncture in the modulation of cravings induced by smoking-related visual cues: an FMRI study - O-Seok Kang; Song-Yi Kim; Geon-Ho Jahng; Hackjin Kim; Jong-Woo Kim; Sun-Yong Chung; Jun-Won Kim; Seung-In Yang; Hi-Joon Park; Hyejung Lee; Younbyoung Chae (Psychopharmacology, 2013)

Gene expression analysis identifies DNA damage-related markers of benzo[a]pyrene exposure in HepG2 human hepatocytes - Mi-Kyung Song; Ji-Seong Yoon; Mee Song; Han-Seam Choi; Chan-Young Shin; Youn-Jung Kim; Woo-In Ryu; Hyo-Sun Lee; Jae-Chun Ryu (Toxicology and Environmental Health Sciences, 2012)

Serum Magnesium Level is Negatively Associated with Fasting Serum Glucose Level in Korean Adults - Chan Hee Song; In Kwon Song; Sang Yhun Ju; Sun Myeong Ock (Biological Trace Element Research, 2011)

Expression of the protective antigen for PEDV in transgenic duckweed, Lemna minor - Suk-Min Ko; Hyeon-Jin Sun; Myung Jin Oh; In-Ja Song; Min-Jae Kim; Hyun-Sook Sin; Chang-Hyo Goh; Yong-Woo Kim; Pyung-Ok Lim; Hyo-Yeon Lee; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2011)

Molecular Analysis of Anthocyanin Biosynthetic Genes and Control of Flower Coloration by Flavonoid 3′,5′-Hydroxylase (F3′5′H) in Dendrobium moniliforme - Sung Soo Whang; Wan Sook Um; In-Ja Song; Pyung Ok Lim; Kyung Choi; Kwang-Woo Park; Kyung-Won Kang; Mi Sun Choi; Ja Choon Koo (Journal of Plant Biology, 2011)

Associations of Serum Ca and Mg Levels with Mental Health in Adult Women Without Psychiatric Disorders - Kyu In Jung; Sun Myeong Ock; Ju Hye Chung; Chan Hee Song (Biological Trace Element Research, 2010)

Test of a convectively forced gravity wave drag parameterization in a general circulation model - Jong-Hun Jeon; Song-You Hong; Hye-Yeong Chun; In-Sun Song (Asia-Pacific Journal of Atmospheric Sciences, 2010)

A novel mutation in Hr causes abnormal hair follicle morphogenesis in hairpoor mouse, an animal model for Marie Unna Hereditary Hypotrichosis - In Cheol Baek; Jeong Ki Kim; Kyu-Hyuk Cho; Dal-Sun Cha; Jae-Woo Cho; Jong Keun Park; Chang-Woo Song; Sungjoo Kim Yoon (Mammalian Genome, 2009)

Buprederm™, a New Transdermal Delivery System of Buprenorphine: Pharmacokinetic, Efficacy and Skin Irritancy Studies - In Park; Dongwon Kim; Jindeog Song; Chang Hoon In; Seung-Wei Jeong; Sang Hun Lee; Bumchan Min; Dongho Lee; Sun-Ok Kim (Pharmaceutical Research, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Fengshui theory in urban landscape planning - Sun-Kee Hong; In-Ju Song; Jianguo Wu (Urban Ecosystems, 2007)

Applications of biotope mapping for spatial environmental planning and policy: case studies in urban ecosystems in Korea - Sun-Kee Hong; In-Ju Song; Byungseol Byun; Sanglim Yoo; Nobukazu Nakagoshi (Landscape and Ecological Engineering, 2005)

Karyotypes of three somaclonal variants and wild plants ofAllium tuberosum by bicolor FISH - Geum-Sook Do; Bong-Bo Seo; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Journal of Plant Biology, 2000)

Ultrastructure of leaves in C4 Cyperus iria and C3 Carex siderosticta - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1999)

Analysis of somaclonal variation through tissue culture and chromosomal localization of rDNA sites by fluorescent in situ hybridization in wild Allium tuberosum and a regenerated variant - Geum-Sook Do; Bong-Bo Seo; Jong-Min Ko; Seon-Hee Lee; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Ultrastructural aspects of leaves inFestuca ovina andPoa sphondylodes (C-3 Poaceae) - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1998)